Technology operating models for Cloud, Edge, and beyond : create your purpose-built technology operating model for single, multi, and hybrid Cloud and Edge /: create your purpose-built technology operating model for single, multi, and hybrid Cloud and Edge. (2023) - Spanner, Andreas; Ponnusamy, Ahilan
No abstract available